2022
DOI: 10.3390/catal12090935
|View full text |Cite
|
Sign up to set email alerts
|

Ring Opening Polymerization of Lactides and Lactones by Multimetallic Titanium Complexes Derived from the Acids Ph2C(X)CO2H (X = OH, NH2)

Abstract: The reactions of the titanium alkoxide [Ti(OR)4] (R = Me, nPr, iPr, tBu) with the acids 2,2’-Ph2C(X)(CO2H), where X = OH and NH2, i.e., benzilic acid (2,2’-diphenylglycolic acid, L1H2), and 2,2’-diphenylglycine (L2H3), have been investigated. The variation of the reaction stoichiometry allows for the isolation of mono-, bi-, tri or tetra-metallic products, the structures of which have been determined by X-ray crystallography. The ability of the resulting complexes to act as catalysts for the ring opening polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…3 New ROP catalysts based on titanium, lithium, zinc, aluminium, and rare-earth metals incorporating the motif Ph 2 C(X) were reported, together with a number of intriguing molecular structures. 4 Recently, for the group V metals, we have investigated the use of niobium and tantalum alkoxide precursors, which afforded tetranuclear complexes [M 4 (OEt) 8 (L 1 ) 4 (μ-O) 2 ] in the case of benzilic acid (L 1 H 2 ), and dinuclear complexes [Nb 2 (OEt) 4 (L 2 H 2 ) 4 (μ-O)] in the case 2,2′-diphenylglycine (L 2 H 3 ). 5…”
mentioning
confidence: 99%
“…3 New ROP catalysts based on titanium, lithium, zinc, aluminium, and rare-earth metals incorporating the motif Ph 2 C(X) were reported, together with a number of intriguing molecular structures. 4 Recently, for the group V metals, we have investigated the use of niobium and tantalum alkoxide precursors, which afforded tetranuclear complexes [M 4 (OEt) 8 (L 1 ) 4 (μ-O) 2 ] in the case of benzilic acid (L 1 H 2 ), and dinuclear complexes [Nb 2 (OEt) 4 (L 2 H 2 ) 4 (μ-O)] in the case 2,2′-diphenylglycine (L 2 H 3 ). 5…”
mentioning
confidence: 99%
“…From the figure, it can be significantly observed that the drug MTD has several obvious diffraction peaks at 2θ from 5 • to 40 • , which are 12.4 • , 14.1 • , 18.2 • , 25.5•, and 27.9 • , respectively, which indicates that the drug MTD has crystalline properties and pure MTD exists in crystalline form. PCL is also crystalline[90], but is semi-crystalline in nature, with a small peak at 2θ at 22.6 • . The XRD images for PVA and other raw materials are amorphous, as indicated by the XRD images of PVA and other raw materials which are relatively smooth and have no obvious diffraction peaks.…”
mentioning
confidence: 99%